Endometriotic Mass After Hysterectomy in a 61 Year Old Post-menopausal Woman: A Case Report and Update - Mathey, Marie Pierre; Bouquet de Jolinière, Jean; Major, Attila; Pugin, Francois; Monnard, Etienne; Fiche, M.; Sandmeier, Daniel; Khomsi, Fathi; Feki, Anis (Frontiers in Surgery, 2019)
Endometriosis is a common, hormone-dependent gynecologic disease. Undiagnosed in large proportion of women, managing therapies depend on the impact of quality of life and includes hormonal treatment and pelvic surgery. Less likely endometriosis can occur in post-menopausal women. Malignant transformation of endometriosis is a rare but well described process, most of time occurring in the ovary, and justifies the practitioner not to underestimate this pathology. We present a case of a 61 year old woman with a symptomatic endometriotic pelvic mass, status post hysterectomy, with no history of endometriosis diagnosed beforehand.